Improving The Competitiveness Of The Main Healthy Work Business Of Srikuncoro Village, Pondok Kelapa Sub-District, Central Bengkulu District (Meningkatkan Daya Saing Usaha Utama Pekerjaan Sehat Desa Srikuncoro Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah) - Chandra, M. Jeffri Arlinandes; Novrianda, Herry; Mikaresti, Pamela; Soleh, Ahmad; Irwanto, Tito; Abi, Yudi Irawan (Indonesia Berdaya, 2025)
Srikuncoro Village is a village located in Pondok Kelapa Sub-district, Central Bengkulu Regency, Bengkulu Province, approximately 16 kilometres from Bengkulu City. Judging from the existing resources, Srikuncoro Village has good potential for the development of small industries, especially household industries in the food sector. One of the small industries in Srikuncoro Village is the Karya Sehat Utama food processing home industry. This industry has strengths in the form of products that have characteristics and potential to be developed. Based on the situation analysis and survey that has been carried out, the proposer and partners agreed on several problems faced, namely limited understanding of legal protection for MSME actors; limited production equipment or technology; limited understanding in managerial aspects (Production, Marketing and Finance); and limited use of information technology in marketing. To overcome these problems, the service team and partners agreed on several solutions to be carried out, namely education on understanding legal protection for MSME actors is expected to improve a healthy and proper business climate among MSME actors to develop rapidly; providing assistance with production equipment or product processing technology to support production capacity according to market needs; education and training in managerial aspects (production management, marketing management and financial management) and training in the use of information technology in online product marketing. In addition, the output of this PkM Lecturer programme will be published in a national journal with ISSN.Abstrak. Desa Srikuncoro merupakan desa yang terletak di Kecamatan Pondok Kelapa, Kabupaten Bengkulu Tengah, Provinsi Bengkulu, kurang lebih 16 kilometer dari Kota Bengkulu. Dilihat dari sumber daya yang ada, Desa Srikuncoro memiliki potensi yang baik untuk pengembangan industri kecil, khususnya industri rumah tangga di bidang pangan. Salah satu industri kecil yang ada di Desa Srikuncoro adalah industri rumah tangga pengolahan pangan Karya Sehat Utama. Industri ini memiliki kekuatan berupa produk yang memiliki ciri khas dan berpotensi untuk dikembangkan. Berdasarkan analisis situasi dan survei yang telah dilakukan, pengusul dan mitra sepakat mengenai beberapa permasalahan yang dihadapi, yaitu keterbatasan pemahaman tentang perlindungan hukum bagi pelaku UMKM; keterbatasan alat atau teknologi produksi; keterbatasan pemahaman dalam aspek manajerial (Produksi, Pemasaran dan Keuangan); dan keterbatasan pemanfaatan teknologi informasi dalam pemasaran. Untuk mengatasi permasalahan tersebut, tim pengabdi dan mitra sepakat mengenai beberapa solusi yang akan dilakukan, yaitu edukasi tentang pemahaman perlindungan hukum bagi pelaku UMKM diharapkan dapat meningkatkan iklim usaha yang sehat dan layak di kalangan pelaku UMKM agar berkembang pesat; pemberian bantuan alat produksi atau teknologi pengolahan produk untuk mendukung kapasitas produksi sesuai kebutuhan pasar; pendidikan dan pelatihan dalam aspek manajerial (manajemen produksi, manajemen pemasaran dan manajemen keuangan) serta pelatihan dalam pemanfaatan teknologi informasi dalam pemasaran produk secara daring. Selain itu, luaran program Dosen PkM ini akan dipublikasikan dalam jurnal nasional ber-ISSN.